Impact of rear wheel axle position on upper limb kinematics and electromyography during manual wheelchair use. Issue 1 (1st January 2018) - Lafta, Hassanain Ali; Guppy, Robert; Whatling, Gemma; Holt, Cathy
Abstract: Manual wheelchair propulsion is an important form of mobility for people with lower limb disabilities. Changes in the wheelchair configuration can affect, range of motion (ROM) of the upper limb joints, muscle actions and system stability. The purpose of this study is to investigate the impact of adjusting wheelchair configurations on upper body joints kinematics and muscle recruitment for able-bodied non experienced manual wheelchair users through applying a marker-based 3D motion analysis technique. Ten healthy male subjects were characterised for three wheelchair configurations, set by adjusting the horizontal axle position of both rear wheels by (3 cm) and (6 cm) posteriorly from the original position set by the manufacturer. Selected 3D kinematic and surface electromyography (sEMG) parameters of the upper body joints and shoulder muscles were measured in the Cardiff University Motion Analysis Laboratory. During the propulsion trials, trunk flexion/extension, lateral bending and axial rotation were evaluated within the average range of (7.50°±1.4°), (5.91°±1.23°) and (7.01°±3.91°), respectively. Dominant shoulder abduction/adduction, flexion/extension and internal/external rotation were evaluated within the average range of (24.63°±6.38°), (17.31°±4.27°) and (40.02°±12.35°), respectively. Dominant elbow pronation/supination and flexion/extension were evaluated within the range of (15.49°±7.70°) and (34.37°±8.38°), respectively. Dominant wrist radial/ulnar deviation and flexion/ extension were evaluated within the average range of (29.82°±8.97°) and (53.59°±9.65°), respectively. With normalising the muscle EMG to the percentage of MVC activity, posterior deltoid had the highest average EMG muscle activity (11.43 ± 5.33) during the propulsion trials and at the three wheel adjustments relative to the other dominant shoulder muscles. Other average muscles activities were evaluated as (6.99 ± 2.37) for upper trapezius, (6.89 ± 2.51) for triceps brachii, (5.39 ± 2.95) for anterior deltoid, (3.26 ± 1.00) for biceps brachii and (3.14 ± 1.26) for pectoralis major as the lowest average activity. The findings of this study indicate that changing rear wheel axle position posteriorly is correlated with increasing the kinematic ROMs of the trunk and dominant upper limb and the sEMG activities of the muscles predominantly involved with the recovery phase of propulsion which could be linked with higher risks of musculoskeletal disorders. This knowledge may help professionals when designing and prescribing wheelchairs that are more proper to users' functional characteristics, accordingly profiting them improved quality of life.